The thermodynamical properties of dS black holes in Einstein gravity with torsion induced by the spinor - Kaya, R.; Ozcelik, H. T. (SPRINGER/PLENUM PUBLISHERS, 2023)
We investigate the thermodynamical properties of de Sitter black holes in (2+1) dimensional Einstein gravity with torsion, induced by spinors. Using the methods of Kraus, Keski-Vakkuri, and Wilczek, we calculate the entropy, temperature, and Hawking radiation from the dS black hole with torsion that has the event and cosmological horizons due to the presence of a positive cosmological constant. We show that the temperatures associated with the event and the cosmological horizons are not equal. We also obtain that the entropies associated with these horizons to differ from the standard Bekenstein-Hawking result.
Keywords: Torsion; dS black hole; Spinor field; Thermodynamics properties; HAWKING RADIATION; SELF-INTERACTION; ENTROPY; SITTER; ENERGY; Astronomy & Astrophysics; Physics